1995
DOI: 10.2136/sssaj1995.03615995005900010006x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Measurement Errors in Time Domain Reflectometry Determinations of Soil Water

Abstract: With the recent development of improved time domain reflectometry (TDR) probe design, measurement systems, and calibration procedures, it is now possible to detect and quantify the effect of temperature on the soil apparent dielectric constant (Ka). We investigated measurement errors in Ka associated with soil temperature variations and compared measured changes in Ka with those predicted by a dielectric mixing model. After confirming the accuracy and resolution of our measurement system with a series of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 0 publications
9
86
1
4
Order By: Relevance
“…9. The majority of tested soils show similar trends that confirm other experimental data (Pepin et al, 1995;. For small and medium moisture values there is a negligible temperature effect and the linear trend lines in Fig.…”
Section: Wwwintechopencomsupporting
confidence: 89%
See 2 more Smart Citations
“…9. The majority of tested soils show similar trends that confirm other experimental data (Pepin et al, 1995;. For small and medium moisture values there is a negligible temperature effect and the linear trend lines in Fig.…”
Section: Wwwintechopencomsupporting
confidence: 89%
“…If bulk soil dielectric permittivity had a temperature dependence related solely to free water, measurements of soil ε b would show a negative correlation with temperature that would increase with water content. Results from Pepin et al (1995) show this negative correlation, www.intechopen.com but the overall changes are smaller than predicted from a dielectric mixing model that integrated the temperature change in dielectric permittivity of water. The same was observed by Halbertsma et al (1995) who made measurements of sand and silt soil samples.…”
Section: Temperature Effect Of Soil Free Water and Electrical Conductmentioning
confidence: 85%
See 1 more Smart Citation
“…Dalton, 1992;Sun et al, 2000;Persson et al, 2000), and temperature (e.g. Pepin et al, 1995;Persson & Berndtsson, 1998). In many cases, the actual physical process that induces the effects on the K a -Q w relationship is not fully understood, although studies have shown that the effects are small in most cases (e.g.…”
Section: Open For Discussion Until 1 December 2001mentioning
confidence: 99%
“…The work of Or and Wraith [1999] is a valuable contribution; it was, however, not available when our paper was published. As stated by CP, the neglect of temperature effects on the TDR readings on soil moisture was based on results presented in one of the few papers on this topic which was available at the time we wrote the paper [Pepin et al, 1995]. We deliberately presented all of our 'raw' data so that others could make use of them in that context, as OW have presented here.…”
mentioning
confidence: 99%